1977
DOI: 10.1159/000158138
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Nicotine Administration on RBC Velocity in Mesenteric Capillaries of the Rat

Abstract: The purpose of this study was to determine the effects of chronic administration of nicotine on red blood cell (RBC) velocity in single capillaries of the mesentery. Ten male rats consumed an average of 2.38 mg nicotine/kg/day, an approximate ‘2 pack’ equivalent, in their drinking water for a period of 15–20 weeks. At the end of this time RBC velocity was measured in single capillaries of the mesentery. The data were compared to RBC velocities measured in a group of matched control rats. Red cell velocities in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

1984
1984
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
1
0
2
Order By: Relevance
“…FHC. This length of NIC treatment has been shown to elicit changes in the vascular system of rats (49,50). Our data showed that the heart's contractility (i.e., ϩdP/dt) increases, while HR, LV pressure, and ϪdP/dt were not affected.…”
Section: Chronic Nicmentioning
confidence: 47%
“…FHC. This length of NIC treatment has been shown to elicit changes in the vascular system of rats (49,50). Our data showed that the heart's contractility (i.e., ϩdP/dt) increases, while HR, LV pressure, and ϪdP/dt were not affected.…”
Section: Chronic Nicmentioning
confidence: 47%
“…A dose utilizada neste estudo (2mg por kg de peso em duas administrações diárias) foi baseada em amostras plasmáticas de humanos tabagistas crônicos. Segundo Richardson et al 18 , é equivalente ao consumo de 60 cigarros ao dia1.…”
Section: Discussionunclassified
“…Outros autores observaram resultados similares. Em estudo sobre o efeito da nicotina na anastomose intestinal de ratos adultos, observou que no 28º dia de pós-operatório houve diminuição da força de ruptura 18 . Avaliou-se a tensiometria em estudo sobre o efeito da nicotina na cicatrização da parede abdominal em ratos adultos, concluiu que no 14º dia há diminuição da força máxima.…”
Section: Discussionunclassified